(untitled) (The Review of Diabetic Studies, 2025)
Background: Fire incidents in healthcare facilities represent critical emergencies that demand rapid, coordinated action to protect vulnerable patients. This systematic review aimed to evaluate the preparedness and response efficiency of healthcare and security personnel during fire emergencies, emphasizing lessons learned, response times, and training interventions. Methods: A systematic search across PubMed, Scopus, Web of Science, Embase, and Google Scholar was conducted following PRISMA 2020 guidelines. Ten peer-reviewed studies (2002–2025) were included, encompassing case reports, cross-sectional surveys, simulation studies, and randomized controlled trials. Data were synthesized narratively, focusing on preparedness levels, training effectiveness, and technological integration. Results: Preparedness levels varied globally, with 52–73% of healthcare staff showing insufficient familiarity with evacuation procedures. Average evacuation times ranged from 3.75 minutes per floor (simulated vertical evacuations) to under 7 minutes in real ICU fires. Structured and online fire safety training programs improved preparedness by 24–30% post-intervention. The integration of simulation modeling and smart fire response systems significantly reduced response times and improved coordination. Major barriers included poor communication, inadequate drills, and lack of coordination with external fire services. Conclusions: Despite advances in training and technology, gaps persist in hospital fire readiness, particularly in staff familiarity, inter-agency coordination, and rapid evacuation of critical patients. Continuous simulation-based training, leadership engagement, and system integration are essential to strengthen fire evacuation preparedness in healthcare facilities.